PENGARUH PENYULUHAN KESEHATAN TERHADAP KEPATUHAN IBU HAMIL ANEMIA DALAM MENGKONSUMSI TABLET FE - Hardaniyati; Dian Soekmawaty Riezqy Ariendha (PROFESSIONAL HEALTH JOURNAL, 2023)
Introduction: Anemia in pregnant women is one of the causes of antenatal bleeding and the prevalence of anemia in pregnant women in the working area of ​​the Sengkol Health Center in 2020 was 23.79%, and increased to 25.88% in 20121, so that it ranks highest for cases of anemia in pregnant women. To determine the effect of providing health education about iron tablets (TTD) for pregnant women on the adherence of pregnant women in consuming iron tablets at Public health center Sengkol. Methods: Pre-experimental research with The One Group Pretest Posttest design. The research sample was pregnant women who met the inclusion and exclusion criteria as many as 30 people with a purposive sampling technique. The intervention was carried out, namely providing counseling in the class of pregnant women at the 3rd meeting for 20 minutes. Data analysis using paired sample test Results: Respondents' characteristics based on the level of adherence before health education, namely low by 24 people (80.0%), after health education the level of adherence was high by 27 people (90.0%). Statistical test results using paired samples test obtained p = 0.000. Conclusion: Health education about iron tablets (TTD) in the class of pregnant women affects the compliance of pregnant women in consuming iron tablets at Public health center Sengkol.